CaO from chicken eggshell supported on activated carbon and KOH (CaO/C/KOH) as catalyst for biodiesel production from off grade palm oil. Issue 1 (February 2021) - Helwani, Z; Zahrina, I; Amraini, S Z; Sianturi, R I; Idroes, G M; Muslem; Idroes, R
Abstract: This study carried out the catalyst synthesis of calcium oxide (CaO) from chicken eggshells supported on activated carbon (C) and activated by KOH solution (CaO/C/KOH). The effects of variation of KOH concentration and the CaO:C mass ratio to catalyst performance were also investigated. The catalyst was used in the biodiesel production from off-grade palm oil. The catalyst with the highest catalytic activity was obtained at the CaO:C mass ratio of 12:6 and the KOH concentration of 25%. The transesterification that was performed under the conditions of the oil: methanol molar ratio of 1:10, the catalyst concentration of 1% -b oil, the reaction temperature of 65 °C, and reaction time of 3 hours produced a biodiesel yield of 85.74%. The catalyst characterization by using XRD, Hammet indicator, and Brunauer-Emmet-Teller (BET) showed the product was in the crystalline phase of CaO, K2CO3, K2O Ca(OH)2, and CaCO3, the base strength of H_> 12.2, and the specific surface area of 17.890 m 2 /g, respectively. The results showed that the KOH concentration in the catalyst activation process was directly proportional to the biodiesel yield. Several methyl esters such as methyl palmitate and methyl oleate were found in biodiesel through Gas Chromatography-Mass Spectrometry (GC-MS) analysis.